Of Men and Demons - Hubley, John; Hubley, Faith (Lightyear, 1993)
Of Men and Demons: In this short, a primal human is eking out an existence on a tiny island- against the best efforts of the gods of wind, rain and lightning. Human ambition and technology battle the powers of fear and superstition, with a surprising twist. [www.bcdb.com]